US drug overdose mortality rose faster among hispanics than non-hispanics from 2010 to 2021. (1st May 2023) - Romero, Ruby; Friedman, Joseph R.; Goodman-Meza, David; Shover, Chelsea L.
Abstract: Background: Historically, overdose mortality rates among Hispanics have been lower than non-Hispanics. The purpose of this analysis was to characterize the U.S. overdose crisis among Hispanics compared to non-Hispanics. Methods: We used the Centers for Disease Control and Prevention Wide-Ranging Online Data for Epidemiological Research (WONDER) platform to obtain drug overdose mortality rates per 100, 000 population between 2010 and 2021 for Hispanics and non-Hispanics. We examined the relative percent change and specific drug involvement (2010–2021) and state-level disparities (2010–2020) among Hispanics versus non-Hispanics. We calculated rate ratios by state and annual percent change in total and for each specific drug. Statistical analyses were performed using R software version 4.0.3 (R Project for Statistical Computing). Results: Nationally, from 2010 to 2021, Hispanic overdose rates rose from 5.6 to 21.7 per 100, 000, an increase of 287.5 % compared to 13.5–35.1 per 100, 000, an increase of 160 % among non-Hispanics. The average annual percent change was 12 % for Hispanics and 9 % for non-Hispanics. The three most common drug classes involved in overdose deaths among both groups included: Fentanyls and synthetic opioids; cocaine; and prescription opioids. Hispanic overdose rates were higher than non-Hispanic rates in New Mexico, Colorado, Massachusetts, and Pennsylvania in 2020, versus only Michigan in 2010. Conclusions: We observed disparities in overdose mortality growth among Hispanics compared to non-Hispanics from 2010 to 2021. These disparities highlight the urgency to develop community-centered solutions that take into consideration the social and structural inequalities that exacerbate the effects of the opioid overdose crisis on Hispanic communities. Highlights: Hispanic overdose rates grew by 287.5 % versus 160 % for non-Hispanics from 2010 to 2021. Hispanic age-adjusted mortality increased from 5.6 per 100, 000 in 2010–21.7 per 100, 000 in 2021. Fentanyl-involved deaths rose 7150 % for Hispanics versus 2052 % for non-Hispanics. Hispanic overdose rates in 2015–2020 rose faster than non-Hispanics in 26/30 states.